2015
DOI: 10.1016/j.nlm.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

From ventral-medial to dorsal-lateral striatum: Neural correlates of reward-guided decision-making

Abstract: The striatum is critical for reward-guided and habitual behavior. Anatomical and interference studies suggest a functional heterogeneity within striatum. Medial regions, such as nucleus accumbens core and dorsal medial striatum play roles in goal-directed behavior, while dorsal lateral striatum is critical for control of habitual action. Subdivisions of striatum are topographically connected with different cortical and subcortical structures forming channels that carry information related to limbic, associativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 42 publications
(77 reference statements)
8
135
0
Order By: Relevance
“…34,45 This could produce a “stop and consider alternate possibilities” mode of responding in situations where reward contingencies had changed. This concept is supported by data showing that septohippocampal lesions increase perseverative responding and proactive interference and decrease fear extinction.…”
Section: Discussionmentioning
confidence: 99%
“…34,45 This could produce a “stop and consider alternate possibilities” mode of responding in situations where reward contingencies had changed. This concept is supported by data showing that septohippocampal lesions increase perseverative responding and proactive interference and decrease fear extinction.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the behavioural dissociation between age and testosterone, and the modelling results, illustrate that impatient behaviour is best described as the product of multiple interacting processes (van den Bos and McClure, 2013). Recent research suggests that the striatum is one of the central regions where different valuation processes are integrated (Burton et al, 2015). Indeed, increased control across adolescence has been associated with the dorsal striatum and its connections with the prefrontal cortex (Luna et al, 2015;van den Bos et al, 2015), whereas sensitivity to immediate rewards in adults has been associated with activity in the ventral striatum (McClure et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Brain activation of the caudate nucleus has been demonstrated during 2DP and decision-making tasks. 40,41 Fiori et al also found that the caudate nucleus contributed significantly to the variation in 2PD in children with PWM lesions. 13 Overall, only low to moderate correlations were found between sensory outcomes and structural brain damage in contrast to motor outcomes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%